Using Reverse-Flow Prefabricated Vascular Structures for Removing Cutaneous Island Flap: An Experimental Study - Öztürk, Güncel; Demiröz, Anıl; Aydın, Yağmur (Cerrahpaşa Medical Journal, 2022)
Objective: While there are studies in the literature on island flap removal using prefabricated vascular structures, there are no experimental studies on island flap removal using reverse-flow prefabricated vascular structures. An island flap using a femoral–saphenous vascular nerve package as a reverse-flow prefabricated vascular carrier experiment was planned for the study. Methods: Twenty-four male Wistar-Albino rats weighing between 250 and 350 g were divided into 4 equal groups. The experiment was carried out in 2 stages. In the first stage, femoral artery (group II) and vein (group III) were ligated separately or both were ligated (group I) to create a reverse-flow flap. Consecutively, the femoral–saphenous vascular nerve package was dissected and prepared to serve as a prefabricated vascular carrier with the aid of the microscope, and the rear area was then transferred under the skin. Results: After the macroscopic observation, the areas living on the skin island were shown. In scintigraphy and in angiographic and histopathological assessments, the presence of blood flow and areas living in the skin island were shown in prefabricated vascular structures. No statistically significant difference was observed in comparisons between the groups (analysis of variance, P > .05). Post-hoc Tukey’s test revealed high similarities between the sham group and group III as well as between group I and group II. Conclusions: The island flap model lifted using the reverse-flow prefabricated vascular structures described for the first time in this experimental study can be accepted as an unusual flap model. Cite this article as: Öztürk G, Demiröz A, Aydın Y. Using reverse-flow prefabricated vascular structures for removing cutaneous island flap: An experimental study. Cerrahpaşa Med J. 2022;46(3):215-222.